2016
DOI: 10.1038/srep23148
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis growth and development requires the activity of host Long-chain Acyl-CoA Synthetases (ACSLs)

Abstract: The obligate-intracellular pathogen Chlamydia trachomatis (Ct) has undergone considerable genome reduction with consequent dependence on host biosynthetic pathways, metabolites and enzymes. Long-chain acyl-CoA synthetases (ACSLs) are key host-cell enzymes that convert fatty acids (FA) into acyl-CoA for use in metabolic pathways. Here, we show that the complete host ACSL family [ACSL1 and ACSL3–6] translocates into the Ct membrane-bound vacuole, termed inclusion, and remains associated with membranes of metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 63 publications
2
50
0
Order By: Relevance
“…Inclusions were imaged by confocal microscopy. Similar to our previous findings (Recuero‐Checa et al, ), Figure S1a shows that LDs are visible in WT and SKO cells. Although we did not observe LDs in SKO cells treated with T863, we did notice that there were some LDs in DKO cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Inclusions were imaged by confocal microscopy. Similar to our previous findings (Recuero‐Checa et al, ), Figure S1a shows that LDs are visible in WT and SKO cells. Although we did not observe LDs in SKO cells treated with T863, we did notice that there were some LDs in DKO cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although others have claimed that LDs are localised within the inclusion and treatment of Ct infected cells with triacsin C, which pharmacologically inhibits LD formation, impairs Ct growth (Cocchiaro et al, ), we found that the effect was due to inhibition of the ACSL family of proteins by triacsin C with no evidence of LDs localising within the inclusion (Recuero‐Checa et al, ). Interestingly, we found that treatment with OA resulted in an increase in Ct inclusion formation even in triacsin C treated cells where LD formation remained inhibited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional reports propose that endogenously synthesize fatty acids are exported out of the C. trachomatis cell and into the chlamydial inclusion, converted to acyl-CoA by the host acyl-CoA synthetase, and used to acylate the deacylated host phospholipids in the inclusion [57,58]. These models for phospholipid synthesis are unprecedented in literature and are not consistent with other experimental results.…”
Section: Pathways For Exogenous Fatty Acid Incorporationmentioning
confidence: 94%